Analisis Kompetensi Aparatur Sipil Negara (ASN) Di Sekretariat Daerah Kabupaten Bengkulu Tengah - Wulan Aprilia; Yusuarsono Yusuarsono; Harius Eko Saputra; Marida Sari Ningsih (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
This study aims to determine the Competency Analysis of State Civil Servants (ASN) at the Regional Secretariat of Central Bengkulu Regency. This research is a qualitative research presented descriptively. There were 6 informants in this study consisting of: 3 key informants and 3 main informants. Data were collected through interviews, observation and documentation The data analysis techniques used were data reduction, data presentation, and drawing conclusions. Based on the results of the research and discussion, it is known that the Competence of Employees at the Regional Secretariat Office of Central Bengkulu Regency has been sufficiently implemented. This can be seen from the several indicators discussed previously, namely: 1. Motive, motivation is carried out in ASN work performance, namely in several ways, including the planning stage, which the stage is taken in an effort to set the expected performance targets for employees and what competencies are expected by the regional secretariat for each employee. 2. Traits, ASN employees have good competence, namely having eight managerial competencies, namely integrity, cooperation, communication, result orientation, public service, self and other development, managing change, and decision making, these must be possessed by ASN to have good competence. 3. Self-Image, employee self-confidence, namely strengthening employee mentality, always motivating employees to hone skills and skills, and being able to control emotions, so that the work given can be completed properly and on time. 4. Social Role, Each employee carries out their respective responsibilities at work, but sometimes there are some employees who are less responsible for their work, many of whom complete their tasks beyond the specified limits. 5. Skill, ASN employees determine procedures for carrying out tasks by complying with Standard Operating Procedures, in which SOPs are guidelines relating to procedures that must be carried out.